Do reflex seizures and spontaneous seizures form a continuum? – Triggering factors and possible common mechanisms. (February 2015) - Irmen, Friederike; Wehner, Tim; Lemieux, Louis
Highlights: Extrinsic triggers in reflex seizures are clearly identifiable. Identification is based on close temporal relationship, high constancy, and reliability. However, triggers can also be intrinsic, complex and multifactorial stimuli. Observability of triggers may vary between reflex and spontaneous seizures. A conceptual continuum of spontaneous and reflex seizures should be considered. Abstract: Recent changes in the understanding and classification of reflex seizures have fuelled a debate on triggering mechanisms of seizures and their conceptual organization. Previous studies and patient reports have listed extrinsic and intrinsic triggers, albeit their multifactorial and dynamic nature is poorly understood. This paper aims to review literature on extrinsic and intrinsic seizure triggers and to discuss common mechanisms among them. Among self-reported seizure triggers, emotional stress is most frequently named. Reflex seizures are typically associated with extrinsic sensory triggers; however, intrinsic cognitive or proprioceptive triggers have also been assessed. The identification of a trigger underlying a seizure may be more difficult if it is intrinsic and complex, and if triggering mechanisms are multifactorial. Therefore, since observability of triggers varies and triggers are also found in non-reflex seizures, the present concept of reflex seizures may be questioned. We suggest the possibility of a conceptual continuum between reflex and spontaneous seizures rather than a dichotomy and discuss evidence to the notion that to some extent most seizures might be triggered.